Role of fibrin D-dimer testing in emergency medicine. Issue 4 (1st July 2003) - Wakai, A; Gleeson, A; Winter, D
Abstract : Objectives: Systemic values of the fibrinolytic plasma marker fibrin D -dimer are raised in a variety of acute clinical conditions. D -dimer values can now be rapidly determined and used to aid diagnosis in emergency medicine. However, despite clinical guidelines, inappropriate and unnecessary measurement of D -dimer values is a significant clinical problem. An understanding of the pathophysiological basis and limitations of the value of D -dimer values may help reduce this problem. This review discusses the pathophysiology of the fibrinolytic system. The currently used assays, clinical indications, and limitations of D -dimer measurement are reviewed. Finally, the potential future clinical indications for measurement of D -dimer values in emergency medicine are discussed. Methods: Literature on D -dimer was identified from Medline, along with cross referencing from the reference lists of major articles on the subject Results and conclusions: Systemic D -dimer values aids diagnosis, and is potentially a prognostic indicator, in a variety of clinical conditions in emergency medicine. However, it has limited specificity in patients with comorbid conditions. Although, currently, there is no standard D -dimer assay, immunoturbidimetric assays are the most suitable for use in emergency medicine